Menakar moralitas elit politik melalui kontrak politik - Nasiwan Nasiwan (Universitas Negeri Yogyakarta, 2004)
Before the General Election to choose the legislative members, that is held on April 5, 2005 and President General Election, that is held on June 5 and September 20, 2004, there was a political phenomenon, which then popularly said